TANTANGAN DAN PELUANG PENDIDIKAN ISLAM DI ERA DIGITAL - Farah Nazilatil Afwa; Ahmad Mustafidin (As-Sulthan Journal of Education, 2025)
Islamic education in the digital era is faced with two sides of the coin: challenges and opportunities. The main challenges lie in the authenticity of content, the digital divide, the quality of education, negative influences, and the lack of digital competence. However, behind that, there are great opportunities in the form of wide accessibility, innovative learning methods, strengthening communities, more effective dissemination of da'wah, and a variety of learning resources. To overcome these challenges and take advantage of these opportunities, collaborative efforts are needed from various parties, including the government, educational institutions, religious leaders, and the community. The development of relevant curricula, improving the digital competence of educators, and strengthening the digital literacy of the community are the keys to the success of Islamic education in the digital era.